Rancang Bangun Aplikasi Analisis Jabatan Dan Beban Kerja Berbasis Web Dengan Framework Codeigniter di Politeknik Perkeretaapian Indonesia Madiun - Ningrum, Putri Dwi Nurismoyo; Nita, Sekreningsih; Nyoto, Edi; Nugrahanti, Fatim (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The rapid development of technology, especially in the fields of electronics and information technology, has provided various conveniences in various aspects of human life. Job analysis has a very important role in human resource management, namely improving organizational performance both in terms of productivity, service and quality to achieve the organization's main goals. This is reflected in several officers who do not match their skills and expertise with their workload, and there are still appointments to positions that meet the specified qualifications, both in terms of education level, rank, skill and experience. The application of job analysis in terms of job descriptions seems to be also experienced the same thing, namely not all the apparatus was placed as expected. Suboptimal implementation of job analysis turns out to have consequences for the performance of the apparatus. The results of this research produce information on positions and workload for each position, thereby assisting Management and Personnel in determining employee needs and employee recruitment. The application in this research was implemented using the PHP programming language and MySQL database.